FAKTOR PENYEBAB TERJADINYA PERCERAIAN PADA MASA PANDEMI COVID-19 DI PENGADILAN AGAMA SAMARINDA - Said, Badrul (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTThis thesis aims to explain the factors that cause divorce cases which have increased due to the Large-Scale Social Restriction (PSBB) policy, as a result of the COVID-19 pandemic that is currently engulfing Indonesia. The government's policy regarding Large- Scale Social Restrictions (PSBB) during the COVID-19 pandemic which aims to maintain family health has turned out to be the cause of an increase in divorce cases. This occurs as a result of the economic impact of this Large-Scale Social Restriction (PSBB) policy. Not a few business actors, both micro and macro, suffered huge losses. As a result, breadwinners have lost their jobs and have no income during the COVID-19 pandemic, and have difficulty getting side jobs or new jobs.This research uses normative- empirical research (applied law research) by using interview study data collection techniques and library research by conducting an assessment of the laws and regulations, books, and scientific journals related to the title of this thesis.The results showed that the reason for the increase in divorce that occurred at the Samarinda City Religious Court was motivated by economic factors, continuous disputes, domestic violence, infidelity, and husbands not working, leaving, not caring and irresponsible. Keywords: Divorce Factor, Large-Scale Social Restriction (PSBB), Covid-19